2010
DOI: 10.1007/s12403-010-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

The Causes and the Control of Selective Pollution of Shallow Wells by Coliform Bacteria, Imo River Basin Nigeria

Abstract: The variability of water quality due to fecal coliform bacteria among shallow wells (37-67 m deep) in Aba northwest and Owerri west flank of the Imo River basin Nigeria surpassed surface explanation. This is because the communities have similar human and animal waste disposing habit. Analytical results show that six out of ten wells (60%) have 40-70FC/100 ml of water exceeding the 10FC/100 ml of water allowable by the world health organization (WHO). The pollution is attributed predominantly to the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Such wells must be monitored by regular water analysis before and after each rain season. Cases of high coliform counts in water collected from shallow wells in the vicinity of mechanic villages due to absence of toilet facilities in the mechanic villages under investigation has been reported (Nwachukwu et al 2010c). Physical observation of iron film coating of water stored in cans, or reddish to rusty color of water cans used by the mechanics due to oxidation of Fe 2+ to Fe 3+ was another clear indicator of metal pollution of some shallow wells near MVs.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Such wells must be monitored by regular water analysis before and after each rain season. Cases of high coliform counts in water collected from shallow wells in the vicinity of mechanic villages due to absence of toilet facilities in the mechanic villages under investigation has been reported (Nwachukwu et al 2010c). Physical observation of iron film coating of water stored in cans, or reddish to rusty color of water cans used by the mechanics due to oxidation of Fe 2+ to Fe 3+ was another clear indicator of metal pollution of some shallow wells near MVs.…”
Section: Resultsmentioning
confidence: 91%
“…Provision of toilet facilities by government owners of the MVs, which may be supported by the mechanics directly or indirectly will reduce incidents of high coliform counts in shallow wells around MVs. Nwachukwu et al (2010c) observed that about 60% of shallow wells within and 500 m in the vicinity of a mechanic village in the Imo River basin have between 40-70 CF/100 ml of coliform, exceeding the 10 CF/100 ml of water allowable by the world health organization. • Have deep water wells or design protected shallow wells in the vicinity of MVs (Nwachukwu et al 2010c).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is important to note that the two communities housing the investigated borrow pits depend on groundwater obtained from shallow wells for their drinking and other domestic uses. These shallow wells have average depth of 44 m, and according to [22], many of these shallow wells supply water of poor quality. There is growing cases of water related diseases mainly around Ihiagwa with higher population density due to the presence of two tertiary institutions.…”
Section: Geotechnical Characteristics Of the Borrow Materialsmentioning
confidence: 99%
“…Nwachukwu et al [8] observed that about 60% of shallow wells within 500 m in the vicinity of Orji and Nekede mechanic villages in the Imo River basin have between 40-70 CF/100 ml of coliform, exceeding the 10 CF/100 ml of water allowable by the world health organization. Be isolated from residential areas in a 50 to 100 year development plan, with farming or vegetable gardens not allowed within and at least 350 m to the MV.…”
Section: Background and Justificationmentioning
confidence: 99%